2017
DOI: 10.1371/journal.pone.0175148
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time interval from diagnosis to treatment on survival for oral cavity cancer: A nationwide cohort study

Abstract: ObjectivesWe aimed to explore the relationship between the time interval from diagnosis to treatment and survival of oral cavity squamous cell carcinoma patients.Materials and methodsA population-based study was conducted between 2004 and 2010. Claims data of oral squamous cell carcinoma patients were retrieved from the Taiwan Cancer Registry Database. Secondary data were obtained from Taiwan’s National Health Insurance Research Database.ResultsA total of 21,263 patients were included in the final analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 27 publications
3
50
0
1
Order By: Relevance
“…Six studies (46%) 10,33,3639 included all head and neck subsites, while 7 studies (54%) were subsite specific (5 oral cavity, 1 oropharynx, and 1 larynx). 19,22,3032,34,35 Four of the studies (31%) 22,31,33,36 did not define the rationale or methods for their definition of prolonged DTI, 4 (31%) 19,35,37,38 used calendar-based categorical definitions (eg, <30 days, 31–60 days), 3 (23%) 30,34,39 used cohort-based quartiles or medians, and 2 (15%) 10,32 used recursive partition analysis to determine an optimal DTI threshold. One study, which exclusively examined cancer of the oral cavity, suggested that DTI of less than 20 days was optimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (46%) 10,33,3639 included all head and neck subsites, while 7 studies (54%) were subsite specific (5 oral cavity, 1 oropharynx, and 1 larynx). 19,22,3032,34,35 Four of the studies (31%) 22,31,33,36 did not define the rationale or methods for their definition of prolonged DTI, 4 (31%) 19,35,37,38 used calendar-based categorical definitions (eg, <30 days, 31–60 days), 3 (23%) 30,34,39 used cohort-based quartiles or medians, and 2 (15%) 10,32 used recursive partition analysis to determine an optimal DTI threshold. One study, which exclusively examined cancer of the oral cavity, suggested that DTI of less than 20 days was optimal.…”
Section: Resultsmentioning
confidence: 99%
“…10 An association between delays in DTI and poorer oncologic outcomes was observed in 9 studies (69%). 10,22,3137 The delayed DTI threshold varied from more than 20 days to 120 days or more. The 4 studies that did not find an association between DTI and survival analyzed thresholds of 50 days or more (vs 24days or less), 45 days or more (vs 30 days or less), and more than 30 days (vs 30 days or less; analyzed in 2 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Time to treatment initiation (TTI) is a proposed national health care metric in the era of quality‐based reimbursement . Previous studies among patients with HNSCC have associated increasing TTI with worsening mortality . This relationship may be multifaceted, with sociodemographic issues, management of comorbid conditions, and complexity of treatment modalities all contributing to increased TTI and decreased overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies among patients with HNSCC have associated increasing TTI with worsening mortality. 5,6 This relationship may be multifaceted, with sociodemographic issues, management of comorbid conditions, and complexity of treatment modalities all contributing to increased TTI and decreased overall survival (OS). It is possible that tumor progression contributes minimally to worsening mortality for those patients experiencing treatment delay, and that expediting care through an already stressed health care system may be a misplaced national emphasis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment delay due to referral time or financial barriers should not occur often in Taiwan. However, some studies still found that cancer patients did not receive prompt treatment upon diagnosis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%